Aplikasi Metode al Miftah Dalam Mendukung Pembelajaran Bahasa Arab : Studi di Kelas VII MTs KH. A Wahid Hasyim Bangil - Fajarudin, Ahmad Aris (Tarbawi : Jurnal Studi Pendidikan Islami, 2022)
Arabic is a language that must be learned by all Muslims in the world. Studying Arabic as a second language will certainly encounter significant difficulties. The differences in terms in Arabic mean that most students do not understand how to use them. Fast learning methods in learning Arabic are increasingly developing. One of them is the al-miftah method. The al-miftah method is used to equate terms in Arabic to Indonesian so that they are easy to understand. For this reason, in this research the researcher wants to combine the al-miftah method into the Arabic language learning process in class VII of Mts KHA Wahid Hasyim Bangil